Inhibition of Inflammasome Activation through the Modulation of b‐hydroxybutyrate Levels In vivo Decreases Alzheimer's Disease Pathology. (20th December 2022) - Shippy, Daniel; Hanslik, Kendra; Wilhelm, Connor; Patel, Viharkumar; Zarbock, Katie R; Bendlin, Barbara B.; Rey, Federico E.; Raife, Thomas; Ulland, Tyler K.
Abstract: Background: Using gnotobiotic models, our research group has demonstrated that specific changes in the gut microbiome modulate serum and brain b‐hydroxybutyrate (BHB) levels. BHB levels measured in blood also differ in Alzheimer's disease (AD), and BHB has been linked with immune function. Recently, microglial activation of the nod‐like receptor family pyrin domain containing protein 3 (Nlrp3) inflammasome—a multi‐protein complex that when activated results in apoptosis specks‐like protein containing a caspase recruitment domain (Asc)‐speck accumulation—has been recognized as feature of AD (extracellular Asc‐specks can nucleate Ab plaques and enhance AD pathology). Given that gut microbiome modulates immune function and may impact inflammasome activation, here we tested the extent to which BHB differs in AD brain, impacts the Nlrp3 inflammasome and impacts AD pathology. Methods: Brain samples and red blood cells from N = 10 individuals with AD and N = 10 controls were obtained from the Wisconsin ADRC and subjected to untargeted metabolomics. For mouse experiments 5XFAD mice, a model for Ab plaque formation, and wild type controls were treated with oral BHB in drinking water. Mice were maintained on BHB drinking water from 8 weeks of age until 4 months of age. Upon harvest half of each mouse brain was fixed, sectioned, stained, and imaged on a confocal microscope. The levels of BHB in the other half of each brain were assessed. Results: We found that individuals with AD have lower levels of BHB in both their red blood cells and their brains. As BHB is known to inhibit Nlrp3 inflammasome activation we hypothesized that increasing BHB levels would result in the inhibition of the Nlrp3 inflammasome and subsequent reduction in AD pathology in vivo . To test this, we administered BHB orally to 5XFAD mice. BHB administration increased brain BHB levels, reduced plaque load, microgliosis, inflammasome activation, and Asc‐spec formation. Conclusions: Our findings demonstrate that BHB levels are lower in the brains of individuals with AD and BHB administration in 5XFAD mice reduces AD pathology by inhibiting Nlrp3 inflammasome activation and Ab plaque formation. Taken together, our data suggest future studies exploring the role of BHB in humans with AD are warranted.